Resurgence of an Inborn Attraction for Animate Objects via Thyroid Hormone T3 - Lorenzi, Elena; Lemaire, Bastien Samuel; Versace, Elisabetta; Matsushima, Toshiya; Vallortigara, Giorgio (Frontiers in Behavioral Neuroscience, 2021)
For inexperienced brains, some stimuli are more attractive than others. Human neonates and newly-hatched chicks preferentially orient towards face-like stimuli, biological motion, and objects changing speed. In chicks, this enhances exposure to social partners, and subsequent attachment trough filial imprinting. Early preferences are not steady. For instance, preference for stimuli changing speed fades away after two days in chicks. To understand the physiological mechanisms underlying these transient responses, we tested whether early preferences for objects changing speed can be promoted by thyroid hormone 3,5,3’-triiodothyronine (T3). This hormone determines the start of imprinting’s sensitive period. We found that the preference for objects changing speed can be re-established in female chicks treated with T3. Moreover, day-one chicks treated with an inhibitor of endogenous T3 did not show any preference. These results suggest that the time windows of early predispositions and of sensitive period for imprinting are controlled by the same molecular mechanisms.